MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR MAHASISWA MELALUI PEMBELAJARAN GENERATIF - Fadli, Fadli (Perspektif Ilmu Pendidikan, 2010)
The research aims at analyzing the quality of studentsâ€™ critical thinking and self-learning abilities by applying generative learning method in the subject of Algebra Structure at Mathematics Education Study Program of STKIP PGRI Lubuk Linggau. The variable of the research was the result of generative learning approach to improve critical thinking and self-learning abilities in the subject of Algebra Structure at Mathematics Education Study Program of STKIP PGRI Lubuk Linggau. The research objects were 23 students of the fifth semester class in Mathematic Education Study Program of STKIP PGRI Lubuk Linggau the year of 2009/2010. Research method applied was quasi experiment, with experiment class treated with generative learning method and without control class. The research result showed that in general, the critical thinking and self-learning abilities of Algebra Structure Subject had the mean of 75.90 (with minimum score of 70) meaning, the critical thinking and self-learning abilities of the students were generally in high level. Whereas the analysis result of variants test was t-count =3.954 and t-table (dk =22, Ã¡ =1%) = 2,508. It showed that the critical thinking and self-learning abilities of the students with generative learning approach in the subject of Algebra Structure at Mathematics Education Study Program of STKIP PGRI Lubuk Linggau was above the score of 70.